2002
DOI: 10.2466/pr0.2002.91.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Attitudes toward Obese People among a Canadian Sample of Men and Women

Abstract: A new scale for examining attitudes toward obese people had 44 items selected from previously published scales designed to indicate attitudes toward obese people. Reliability analysis yielded a Cronbach coefficient alpha of .92 for the total sample. A factor analysis yielded four factors. Employing the Body Mass Index as an indicator of obesity, the attitudes of 239 men and women were examined. Women were significantly more positive than men in their attitude toward obese people. When examining Body Mass Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…2007). In the general population, Glenn and Chow (2002) found no differences in attitudes towards obese persons based on BMI alone, but did find that obese women had more positive attitudes than obese men and that overall, female participants had more positive attitudes. Similarly, Robinson et al.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2007). In the general population, Glenn and Chow (2002) found no differences in attitudes towards obese persons based on BMI alone, but did find that obese women had more positive attitudes than obese men and that overall, female participants had more positive attitudes. Similarly, Robinson et al.…”
Section: Discussionmentioning
confidence: 56%
“…1989, Robinson et al. 1993, Culbertson & Smolen 1999, Glenn & Chow 2002) and the current study is unable to further clarify the issue. Culbertson and Smolen (1999) found no difference in nurses’ attitudes towards obese patients among nurses who were overweight themselves and although Bagley et al.…”
Section: Discussionmentioning
confidence: 57%
“…For example, Allison et al. (1991) found that found that men held more positive attitudes, whilst Morrison and O'Connor (1999) and Glenn and Chow (2002) found that women were more positive. Equally variable have been findings about how an individual's own body weight affects attitudes (Price et al.…”
Section: Discussionmentioning
confidence: 99%
“…Aussi, les participantes répondaient-elles en se positionnant comme membre du groupe auquel elles appartenaient (i.e., les étudiants de l'université), mais aussi du fait de la référence au groupe des hommes de leur université, nous les placions, à la fois en contexte endogroupal et en contexte de comparaison sociale exogroupale. L'intérêt de placer les participantes à la place d'étudiants hommes réside surtout dans le fait que les hommes semblent avoir une attitude plus négative que les femmes concernant l'obésité et les personnes obèses (Crandall, 1994 ;Glenn & Chow, 2002 ;Lewis, Cash, Jacobi, & Bubb-Lewis, 1997 ;Morrison & O'Connor, 1999 ;Perez-Lopez, Lewis, & Cash, 2001). En procédant ainsi, nous laissions aux participantes la possibilité de libérer l'expression de pensées contre-normatives relatives à l'obésité.…”
Section: Procédure Et Matérielunclassified